APLIKASI KONSEP DAN KAIDAH ISTISHHÂB DALAM HUKUM EKONOMI SYARIAH - Panji Adam Agus Putra (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2021)
The scholars agree that the agreed upon sources of law in Islamic teachings are the Qur'an and the Sunnah. However, they have different opinions regarding ra'yu or logic in terms of being a source of law. One form of ra'yu disputed by scholars in the study of ushul fiqh is istishhâb. Simply put, istishab is the persistence of something as long as nothing else changes it. The purpose of this study was to determine the rules of fiqh related to istishhâb as well as the application and implementation of the concept and rules of istishhâb in sharia economic law. The results of the study indicate that the concept of istishhâb is based on the basic principle of belief which reads as al-yaqȋn lâ yuzâl bi al-syak” which means that belief cannot be dispelled because of doubt. The application of istishhâb concepts and rules in the field of sharia economic law is implemented in, first, debt-receivable disputes; second, the allegation of recording on the object of the sale-purchase contract; third, business profit reports; and fourth, the validity of multiple contracts (al-'uqȗd al-murakkabah).